Analysis and seismic behavior verifacation of Zipingpu concrete faced rock-fill dam during Wenchuan Earthquake. Issue 4 (September 2019) - Zhao, Mengdie; Han, Liwei; Zhang, Xianlei; Li, Zongkun
Abstract: Based on the seismic damage of the Zipingpu dam in Wenchuan earthquake, the stochastic finite fault method with dynamic corner frequency is used to reconstruct the ground motion input acceleration time history of the Zipingpu dam in Wenchuan earthquake, and the dam-base-water seismic response analysis model is established. After analyzing the causes of dam deformation and panel joint dislocation after the earthquake, this paper suggested the comprehensive anti-seismic measures to improve the panel stress. These measures have important theoretical and practical significance for preventing the slab damage caused by extreme earthquakes in the concrete faced rock-fill dam (CRFD).